2014
DOI: 10.15282/ijame.10.2014.12.0163
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Injection Timing on the Performance of a Diesel Engine Using Diesel-Biodiesel Blends

Abstract: In this study, the effect of fuel injection timing on the performance of a diesel engine was investigated experimentally and analytically using diesel-biodiesel blends. Different experiments were carried out on the diesel engine at engine speeds of 1200, 1600, 2000 and 2400 rpm. The injection timing was regulated for 10, 15 and 20 degree crank angle before top dead centre. The experimental results of engine torque, brakespecific fuel consumption (BSFC), cylinder pressure, and exhaust gas temperature for fuel b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 38 publications
2
25
0
Order By: Relevance
“…Biodiesel has low sulphur content, low aromatic content and oxygen containing compounds due to which the emissions of SO2, CO2, HC and PM are reduced. Besides, it has good ignition ability in engine owing to its high cetane number compared to that of conventional diesel fuel [10,[18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Biodiesel has low sulphur content, low aromatic content and oxygen containing compounds due to which the emissions of SO2, CO2, HC and PM are reduced. Besides, it has good ignition ability in engine owing to its high cetane number compared to that of conventional diesel fuel [10,[18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…This increasing energy demand should be met by a cleaner source of energy [3,4]. Biodiesel is made from renewable plant or animal fats (tallow) that contain fatty acids [5][6][7][8], which can be converted into biodiesel using the transesterification reaction [9,10]. Biodiesel can also be produced from a wide array of feedstocks such as waste cooking oil, edible and non-edible oil seeds, wood and wood waste etc.…”
Section: Introductionmentioning
confidence: 99%
“…If injection starts later (retarded injection timing), air temperature and pressure are slightly higher initially, and a decrease in ignition delay would occur. This means that injection timing variation has a strong effect on ignition delay, and consequently on engine combustion and emissions because of the changing maximum pressure and temperature in engine cylinder [14]. Patil and Thipse [11] reported that the addition of DEE to diesel fuel causes retardation of dynamic injection timing due to problems encountered with fuel pump and lowers density and viscosity of DEE-diesel blends.…”
Section: Introductionmentioning
confidence: 99%